2019
DOI: 10.1136/bmjopen-2018-022710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ramadan fasting on kidney function and related outcomes in patients with chronic kidney disease: a systematic review protocol

Abstract: IntroductionFasting during the month of Ramadan is a significant Islamic religious practice that involves abstinence from food, drink and medication from dawn to dusk. As just under a quarter of the world’s population identifies as Muslim, the effect of fasting on chronic conditions, such as chronic kidney disease (CKD) is a topic of broad relevance. To date, the information in this area has been mixed, with many limitations of previous studies. This study aims to synthesise the evidence of the effect of Ramad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…RF is performed from dawn to sunset for 29–30 days. Due to geographical differences, the time periods of RF vary from 9 to 22 h per day ( 2 ). In this study, RF was performed for 17–18 h/day.…”
Section: Introductionmentioning
confidence: 99%
“…RF is performed from dawn to sunset for 29–30 days. Due to geographical differences, the time periods of RF vary from 9 to 22 h per day ( 2 ). In this study, RF was performed for 17–18 h/day.…”
Section: Introductionmentioning
confidence: 99%
“…These two meta-analyses were conducted in 2014 and 2015, respectively. More recently, Bello et al [ 20 ] published their protocol for a systemic review in 2019, but the final results have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ramadan intermittent fasting (RIF) is one type of IF that performed by about 1.5 billions of Muslims worldwide annually from dawn to sunset for one month. The time periods of RIF vary from 9 to 22 h per day due to geographical differences and seasonal variation ( 4 ). Food, water, smoking and sexual activities are forbidden during the fasting daytime hours of Ramadan month.…”
Section: Introductionmentioning
confidence: 99%